It started with a tweet - Bell, Anna (London Zaffre Publishing, 2017)
"Daisy Hobson lives her whole life online. A marketing manager by day, she tweets her friends, instagrams every meal and arranges (frankly, appalling) dates on Tinder. But when her social media obsession causes her to make a catastrophic mistake at work, Daisy finds her life going into free-fall. Her sister Rosie thinks she has the answer to all of Daisy's problems - a digital detox in a remote cottage in Cumbria
1
Keywords: Social media -- Fiction